2017
DOI: 10.1108/ejm-10-2014-0633
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity in branding – exploring antecedents and consequences of brand authenticity

Abstract: Purpose Consumer demand for authentic brands is steadily rising. With increased pressure to accommodate this demand, researchers and marketers seek to understand how to influence a brand’s perceived authenticity. The purpose of this paper is to build a link between previous research on authenticity and thus gain a deeper understanding of the influencing factors of brand authenticity and its consumer outcomes. Design/methodology/approach Building on an extensive literature review, the authors identify various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
333
1
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(378 citation statements)
references
References 65 publications
(112 reference statements)
28
333
1
16
Order By: Relevance
“…Schallehn et al () highlight the role of brand consistency and continuity in infusing a brand with authenticity. Based on an extensive literature review, Fritz et al () validate antecedents of brand authenticity as the latter relate to a brand's past (e.g., brand nostalgia), values (e.g., brand social commitment), and consumer self‐identification with a brand (e.g., brand self‐congruence).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Schallehn et al () highlight the role of brand consistency and continuity in infusing a brand with authenticity. Based on an extensive literature review, Fritz et al () validate antecedents of brand authenticity as the latter relate to a brand's past (e.g., brand nostalgia), values (e.g., brand social commitment), and consumer self‐identification with a brand (e.g., brand self‐congruence).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Second, the process through which brand authenticity is created by brands remains underexplored. Although some work provides for an understanding of the antecedents of brand authenticity (Fritz et al, ; Morhart et al, ), researchers shed little or no light on how brands can use this knowledge to develop coherent practices intended to shape perceptions of authenticity, especially in the early stages of brand development. In reaction to these observations, this research poses the following questions: How do consumers develop perceptions of authenticity as the latter relate to young brands?…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hochschild (1983), workers in airline cabins seek control in order to reaffirm their identity as professional, skilled individuals. Fritz et al (2017) found that authenticity has positive consequences for products' success. Napoli et al (2016) indicated that authenticity cues of quality commitment, heritage and sincerity have differential effects on a brand's position along the authenticity continuum and, consequently, authenticity strategies.…”
Section: Dimensionsmentioning
confidence: 99%
“…Customers are well-known to value the extra effort made by a company to help them in their decision-making process (Fritz et al, 2017;Park et al, 2010;Pechmann, 1992;Trifts and Häubl, 2003). As customers see that a company's interests and perspectives are aligned with their own, they may begin to view the company as part of their self (Aron et al, 1991;Park et al, 2016).…”
Section: Business Transparency and Customer Sustainable Responsible mentioning
confidence: 99%